Evaluation of the relationship between polymorphisms in CYP2C19 and the single‐dose pharmacokinetics of omeprazole in healthy Chinese volunteers: A multicenter study - Shuang Zhou; Ran Xie; Xiaodan Zhang; Xu He; Jie Huang; Yin Jungang; Man Liao; Ying Ding; Dandan Yang; Ying Liu; Qian Zhang; Guoping Yang; et al. (Wiley, 2022)
Abstract The aim of this study was to evaluate the relationship between polymorphisms in CYP2C19 and the single‐dose pharmacokinetics (PKs) of omeprazole in healthy Chinese volunteers. A 20 mg single dose of omeprazole (Losec) enteric‐coated capsules or tablets was orally administered to 656 healthy subjects from eight subcenters. The polymorphic alleles of CYP2C19*2, *3, and *17 were determined by Sanger sequencing and Agena mass array. Plasma concentrations of omeprazole were determined by high‐performance liquid‐chromatography tandem mass spectrometry. PK parameters of area under the concentration versus time curve (AUC)0‐t, AUC from zero to infinity (AUC0‐∞), maximum plasma concentration (Cmax), and terminal half‐life (t1/2) were significantly influenced by CYP2C19 phenotype (all p < 0.001) and diplotype (all p < 0.001), and the same results were obtained in the subgroup analysis of the effects of diet and dosage form. The polymorphisms of CYP2C19*2(rs4244285; all PK parameters p < 0.001) and *3(rs4986893; pCmax = 0.020, and the p values of other PK parameters were less than 0.001) were significantly associated with the PKs of omeprazole. For CYP2C19*17 (rs12248560), only t1/2 showed a significant correlation (p = 0.032), whereas other PK parameters did not. The present study demonstrated that the Pks of omeprazole is greatly influenced by CYP2C19.